Evaluating social support, work-family enrichment and life satisfaction among nurses in Malaysia - Wan Rashid, Wan Edura; Nordin, Mohamad Sahari; Omar, Azura; Ismail, Izhairi (2011)
The purpose of the present study was to validate the hypothesized interrelationships among the constructs of social support, work-family enrichment and life satisfaction among nurses of public hospitals in Malaysia. This study also examined the likely mediation effect of work-family enrichment on support-satisfaction relationship. The primary data collection tool for the quantitative study was a questionnaire which was administered to 689 nurses employed in public hospitals in Malaysia. A full structural modeling testing were used in SEM with AMOS 17 data-fitting program, supported the hypothesized relationship. The results established statistically substantial and significant path coefficients.